Positive electrode material and preparation method thereof, battery and electric device

By mixing the metal salt solution and the organic ligand solution to form a metal organic skeleton compound precursor, the agglomeration problem after calcination of the positive electrode material is solved, uniform mixing and sintering of lithium salts is achieved, and the circulation performance and life of the battery are improved.

CN119191378APending Publication Date: 2024-12-27GUANGZHOU AUTOMOBILE GROUP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411148344.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the prior art, large-area agglomeration is prone to occur after the precursor is calcined during the preparation of the positive electrode material, resulting in poor particle dispersion, affecting the uniformity of lithium salt mixing and battery circulation performance.

Method used

By mixing the metal salt solution and the organic ligand solution, it forms a metal organic framework compound (MOFs) precursor, with a moderate spherical particle size and is not easy to agglomerate during the calcination process. It is sintered with lithium salt to reduce intra-crystal microcracks and improve battery circulation performance .

Benefits of technology

The precursor and lithium salt are fully and uniformly mixed, the performance of the positive electrode material and the circulation performance of the battery are improved, and the life of the battery is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191378A_ABST
    Figure CN119191378A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a preparation method thereof, a battery and an electric device. The preparation method of the positive electrode material comprises the following steps: preparing a metal salt solution and an organic ligand solution; mixing the metal salt solution and the organic ligand solution to form a turbid liquid; carrying out solid-liquid separation on the turbid liquid to separate out a precursor; the precursor is dried to obtain a precursor, and the precursor comprises a metal organic framework compound; and calcining the precursor, mixing with a lithium salt, and sintering to obtain the positive electrode material. According to the preparation method of the positive electrode material provided by the embodiment of the invention, the formed precursor comprising the metal organic framework compound (MOFs) is moderate in spherical particle size, less prone to large-area agglomeration in the calcining process and relatively good in dispersity, so that the calcined precursor can be more fully and uniformly mixed with a lithium salt, and the lithium ion battery performance is improved. The performance of the prepared positive electrode material is better; and moreover, intragranular microcracks can be reduced, so that the cycle performance of the battery is better.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode material and a preparation method thereof, a battery and an electrical device. Background Art

[0002] In the related art, when preparing positive electrode materials, the precursor prepared is prone to large-area agglomeration after calcination, and the particle dispersion is poor, which will lead to uneven mixing of the precursor and the lithium salt, affecting the subsequent sintering after the precursor and the lithium salt are mixed, thereby affecting the performance of the prepared positive electrode material; and the positive electrode material prepared by the preparation method in the related art has poor battery cycle performance. Therefore, there is room for improvement. Summary of the invention

[0003] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, one purpose of the present invention is to propose a method for preparing a positive electrode material, by mixing a metal salt solution and an organic ligand solution, and then separating and drying, a precursor including a metal organic framework compound (MOFs) is formed, the spherical particle size is moderate, it is not easy to agglomerate in a large area during the calcination process, and the dispersibility is good, so that the calcined precursor and the lithium salt can be mixed more fully and evenly, and then the lithiation reaction can be better carried out during the subsequent sintering of the precursor and the lithium salt, so that the performance of the prepared positive electrode material is better; and the positive electrode material prepared by the preparation method can reduce intracrystalline microcracks, so that the cycle performance of the battery is better.

[0004] The present invention also provides a positive electrode material prepared by the positive electrode material preparation method.

[0005] The invention also provides a battery having the positive electrode material.

[0006] The invention also provides an electrical device having the battery.

[0007] According to a first aspect of an embodiment of the present invention, a method for preparing a positive electrode material comprises: preparing a metal salt solution and an organic ligand solution; mixing the metal salt solution and the organic ligand solution to form a suspension; performing solid-liquid separation on the suspension to separate a precursor; drying the precursor to obtain a precursor, wherein the precursor comprises a metal organic framework compound; calcining the precursor; mixing the calcined precursor with a lithium salt, and sintering the mixture to obtain the positive electrode material.

[0008] According to the method for preparing the positive electrode material of an embodiment of the present invention, a precursor including a metal organic framework compound (MOFs) is formed by mixing a metal salt solution and an organic ligand solution, and then separating and drying them. The spherical particle size is moderate, large-area agglomeration is not likely to occur during the calcination process, and the dispersion is good. In this way, the calcined precursor and the lithium salt can be mixed more fully and evenly, and then the lithiation reaction can be better carried out during the subsequent sintering of the precursor and the lithium salt, so that the performance of the prepared positive electrode material is better; and the positive electrode material prepared by this preparation method can reduce intracrystalline microcracks, so that the battery cycle performance is better.

[0009] According to some embodiments of the present invention, before drying the precursor, the precursor is washed with an organic solvent.

[0010] According to some embodiments of the present invention, washing the precursor with an organic solvent comprises:

[0011] The precursor is washed with N,N-dimethylformamide and ethanol respectively.

[0012] According to some embodiments of the present invention, the calcined precursor and the lithium salt are mixed and sintered, comprising:

[0013] In an oxygen atmosphere, the temperature is increased to a first set temperature at a set heating rate, and sintered at the first set temperature for a first set time.

[0014] According to some embodiments of the present invention, the set heating rate ranges from 3°C / min to 8°C / min; the first set temperature ranges from 750°C to 900°C; and the first set time ranges from 6h to 10h.

[0015] According to some embodiments of the present invention, calcining the precursor includes: calcining at a second set temperature for a second set time;

[0016] The second set temperature ranges from 400° C. to 600° C., and the second set time ranges from 2 h to 4 h.

[0017] According to some embodiments of the present invention, mixing the precursor and the lithium salt comprises: grinding and mixing the lithium salt and the calcined precursor.

[0018] According to some embodiments of the present invention, the drying process conditions for drying the precursor include: drying at a third set temperature for a third set time;

[0019] The third set temperature ranges from 50°C to 70°C, and the third set time ranges from 10h to 14h.

[0020] According to some embodiments of the present invention, the molar ratio of lithium ions in the lithium salt to metal ions in the metal salt solution is 1.02-1.08; and / or the concentration range of the metal salt solution is 1 mol / L-2 mol / L.

[0021] According to some embodiments of the present invention, preparing the metal salt solution comprises: dissolving a soluble metal salt in N,N-dimethylformamide at a fourth set temperature, wherein the fourth set temperature ranges from -20°C to 60°C;

[0022] The method for preparing the organic ligand solution comprises: dissolving an organic ligand raw material in N,N-dimethylformamide at a fourth set temperature.

[0023] According to some embodiments of the present invention, the fourth set temperature range is -5°C to 30°C.

[0024] According to some embodiments of the present invention, mixing the metal salt solution and the organic ligand solution comprises:

[0025] pouring the metal salt solution into the organic ligand solution;

[0026] The mixture is stirred at a set speed for a fourth set time, wherein the set speed ranges from 400 rpm to 600 rpm, and the fourth set time ranges from 0.5 h to 1.5 h.

[0027] According to some embodiments of the present invention, the lithium salt includes at least one of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium acetate and lithium oxalate.

[0028] According to some embodiments of the present invention, the metal salt in the metal salt solution includes soluble nickel salt, cobalt salt and manganese salt; the organic ligand raw material in the organic ligand solution includes terephthalic acid.

[0029] According to some embodiments of the present invention, the nickel salt includes at least one of nickel sulfate, nickel acetate, nickel nitrate and nickel chloride; the cobalt salt includes at least one of cobalt sulfate, cobalt acetate, cobalt nitrate and cobalt chloride; the manganese salt includes at least one of manganese sulfate, manganese acetate, manganese nitrate and manganese chloride.

[0030] According to the positive electrode material of the second embodiment of the present invention, the positive electrode material is prepared by the preparation method of the first embodiment of the present invention, the positive electrode material is a single crystal structure and the chemical formula of the positive electrode material is LiNi x Co y Mn z O2, where 0 <x<1,0<y<1,0<z<1,x+y+z=1。

[0031] The positive electrode material according to the embodiment of the present invention is prepared by using the preparation method according to the embodiment of the first aspect of the present invention. The precursor is not easy to agglomerate after sintering and has good dispersibility. The positive electrode material has fewer intracrystalline microcracks, which makes the battery cycle performance better.

[0032] A battery according to an embodiment of the third aspect of the present invention comprises: a battery case; an electrode group, which is arranged in the battery case and comprises a stacked positive electrode sheet and a negative electrode sheet, the positive electrode sheet comprises a positive electrode collector and a positive electrode active material layer coated on the positive electrode collector, and the positive electrode active material layer comprises the positive electrode material according to the embodiment of the second aspect of the present invention.

[0033] According to the battery of the embodiment of the present invention, by including the positive electrode material according to the embodiment of the second aspect of the present invention, the precursor of the positive electrode material is not easy to agglomerate after sintering, has good dispersibility, and has fewer intracrystalline microcracks in the positive electrode material, so that the battery has better cycle performance.

[0034] An electrical device according to an embodiment of a fourth aspect of the present invention comprises: a battery according to an embodiment of the third aspect of the present invention.

[0035] The electric device according to the embodiment of the present invention comprises the battery according to the embodiment of the third aspect of the present invention, so the battery has better cycle performance and longer life.

[0036] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0038] Figure 1 It is an XRD graph obtained by performing XRD test on the precursors before calcination of Example 1, Example 2, Example 3 and the precursor before calcination of Comparative Example 1.

[0039] Figure 2 is a crystal structure diagram of the precursor in Example 1 before calcination;

[0040] Figure 3 is a SEM picture of a precursor before calcination prepared according to the preparation method of some embodiments of the present invention, Figure 3 (a) is a SEM image of the precursor before calcination in Example 1, Figure 3 (b) is a SEM image of the precursor before calcination in Example 2, Figure 3 (c) is a SEM image of the precursor before calcination in Example 3;

[0041] Figure 4This is the XRD of the positive electrode material prepared according to the preparation method of some embodiments of the present invention. Figure 4 (a) is the full XRD spectrum, Figure 4 (b) is the spectrum of the (006) / (102) diffraction peak area, Figure 4 (c) is a (018) / (110) diffraction peak region spectrum, and Figures (d), (e) and (f) are XRD refined spectra of Example 1, Example 2 and Example 3, respectively;

[0042] Figure 5 This is a SEM image of a positive electrode material prepared by a preparation method according to some embodiments of the present invention;

[0043] Figure 6 XPS spectra of positive electrode materials prepared by the preparation methods according to some embodiments of the present invention;

[0044] Figure 7 is a characterization diagram of the positive electrode material of Example 1, wherein Figure 7 (a) is the TEM image of Example 1, Figure 7 (b) is an enlarged TEM image of Example 1, Figure 7 (c) Figure 7 (d) is the IFFT diagram of Example 1, Figure 7 (e) is the HRTEM image of Example 1, Figure 7 (f) is the Mapping diagram of Example 1, Figure 7 (g) is the selected area electron diffraction pattern of Example 1;

[0045] Figure 8 The cycle performance diagram of the positive electrode material prepared according to the preparation method of some embodiments of the present invention and the positive electrode material of Comparative Example 1 at 25° C.

[0046] Fig. 9 The cycle performance diagram of the positive electrode material prepared according to the preparation method of some embodiments of the present invention and the positive electrode material of Comparative Example 1 at 45° C.

[0047] Fig.10 These are cross-sectional SEM images of the button batteries in Example 1 and Comparative Example 1 after 200 cycles, where (a) and (b) are from Example 1, and (c) and (d) are from Comparative Example 1. DETAILED DESCRIPTION

[0048] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0049] A method for preparing a positive electrode material according to an embodiment of the first aspect of the present invention comprises:

[0050] Preparing a metal salt solution and an organic ligand solution. For example, the prepared positive electrode material is a ternary positive electrode material. The metal salt solution may include a plurality of transition metal ions. The plurality of transition metal ions include a first transition metal ion, a second transition metal ion, and a third transition metal ion. For example, the first transition metal ion may be a nickel ion, the second transition metal ion may be a cobalt ion, and the third transition metal ion may be a manganese ion.

[0051] The metal salt solution and the organic ligand solution are mixed to form a suspension. By mixing and reacting the metal salt solution and the organic ligand solution, the precursor obtained in the subsequent step can include a metal organic framework compound. This method makes the preparation process of the precursor relatively simple and easy to control, so that the particle size of the prepared precursor can be better controlled, so that a precursor with a relatively uniform and moderate particle size can be obtained;

[0052] Performing solid-liquid separation on the suspension to separate the precursor, for example, centrifugal separation can be used to perform solid-liquid separation on the suspension;

[0053] The precursor is dried to obtain a precursor, the precursor includes a metal organic framework compound, and the precursor including a metal organic framework compound (MOFs) can be obtained by mixing a metal salt solution and an organic ligand solution to react. In the process of preparing the precursor, the particle size of the generated precursor can be controlled by controlling the reaction temperature, so that the process of making the positive electrode material is simpler. By controlling the particle size of the generated precursor, the particle size of the precursor is moderate and uniform;

[0054] The precursor is calcined, and the precursor needs to be mixed with lithium salt for sintering. If carbon-containing organic matter is still retained in the precursor, the carbon element will be converted into carbon dioxide during the sintering process, and most lithium salts such as lithium hydroxide can react with carbon dioxide. By calcining the precursor, the carbon-containing organic matter in the precursor can be removed, avoiding the generation of carbon dioxide and the reaction with lithium salt to waste lithium raw materials; and, since the particle size of the generated precursor is controlled in the early preparation process, the particle size of the precursor is moderate and uniform, and the precursor is not easy to agglomerate during the calcination process, and has good dispersibility;

[0055] The calcined precursor and lithium salt are mixed and sintered to obtain a positive electrode material. Since the precursor is not easy to agglomerate during the calcination process and has good dispersibility in the above steps, the calcined precursor and lithium salt can be mixed more fully, and then the lithiation reaction can be better carried out during the subsequent sintering of the precursor and the lithium salt, so that the performance of the prepared positive electrode material is better, thereby making the battery cycle performance better.

[0056] The prepared positive electrode material is a single crystal positive electrode material, for example, a single crystal ternary positive electrode material.

[0057] According to the method for preparing the positive electrode material of an embodiment of the present invention, a precursor including a metal organic framework compound (MOFs) is formed by mixing a metal salt solution and an organic ligand solution, and then separating and drying them. The spherical particle size is moderate, large-area agglomeration is not likely to occur during the calcination process, and the dispersion is good. In this way, the calcined precursor and the lithium salt can be mixed more fully and evenly, and then the lithiation reaction can be better carried out during the subsequent sintering of the precursor and the lithium salt, so that the performance of the prepared positive electrode material is better; and the positive electrode material prepared by this preparation method can reduce intracrystalline microcracks, so that the battery cycle performance is better.

[0058] According to some embodiments of the present invention, before drying the precursor, the precursor is washed with an organic solvent. By washing the precursor with an organic solvent, unreacted substances on the surface of the precursor can be washed away.

[0059] According to some embodiments of the present invention, washing the precursor with an organic solvent includes: washing the precursor with N,N-dimethylformamide and ethanol, respectively. For example, the precursor can be washed with N,N-dimethylformamide (DMF) first. Since N,N-dimethylformamide is a solvent for metal salt solutions and organic ligand solutions, and has a high solubility for metal salts and organic ligands, N,N-dimethylformamide can fully wash away the unreacted substances on the surface of the precursor; then, the precursor is washed with ethanol, and ethanol can wash away the N,N-dimethylformamide on the surface of the precursor.

[0060] According to some embodiments of the present invention, the calcined precursor and lithium salt are mixed and sintered, including: heating to a first set temperature at a set heating rate under an oxygen atmosphere, and sintering at the first set temperature for a first set time.

[0061] Optionally, the range of the heating rate is set to 3°C / min to 8°C / min; for example, the set heating rate may be 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, etc. The range of the first set temperature is 750°C to 900°C, for example, the first set temperature may be 750°C, 800°C, 850°C, 900°C, etc. The range of the first set time is 6h to 10h, for example, the first set time may be 6h, 7h, 8h, 9h, 10h, etc. For example, the calcined precursor and lithium salt are mixed and sintered, including: heating to 900°C at a rate of 5°C / min under oxygen conditions, and sintering at 900°C for 8h.

[0062] According to some embodiments of the present invention, calcining the precursor includes: calcining at a second set temperature for a second set time. The second set temperature ranges from 400°C to 600°C, and the second set time ranges from 2h to 4h. By making the second set time not less than 2h, the organic matter in the precursor can be fully calcined to prevent the subsequent generation of carbon dioxide and the lithium salt from reacting with the lithium salt; by making the second set time not more than 4h, the process time can be shortened while ensuring that the precursor is fully calcined.

[0063] According to some embodiments of the present invention, mixing the precursor and the lithium salt includes grinding and mixing the lithium salt and the calcined precursor. By grinding and mixing the calcined precursor and the lithium salt, the lithium salt and the precursor can be dispersed and mixed more fully and uniformly.

[0064] According to some embodiments of the present invention, the drying process conditions for drying the precursor include: drying at a third set temperature for a third set time. By drying the precursor, organic matter used for washing on the surface of the precursor, such as ethanol, can be preliminarily removed.

[0065] The third set temperature ranges from 50°C to 70°C, and the third set time ranges from sintering 10h to 14h. By setting the third set time to be not less than 10h, the precursor can be dried more fully; by setting the third set time to be not more than 14h, time can be avoided while ensuring that the precursor is fully dried, thereby improving production efficiency.

[0066] According to some embodiments of the present invention, the molar ratio of lithium ions in the lithium salt to metal ions in the metal salt solution is 1.02 to 1.08. By making the molar ratio of lithium ions in the lithium salt to metal ions in the metal salt solution not less than 1.02, it is possible to ensure that there are sufficient lithium ions in the lithium salt and improve the specific capacity of the battery; by making the molar ratio of lithium ions in the lithium salt to metal ions in the metal salt solution not greater than 1.08, it is possible to avoid the waste of lithium ions caused by the inability of excess lithium ions to provide functions.

[0067] According to some embodiments of the present invention, the concentration of the metal salt solution ranges from 1 mol / L to 2 mol / L. For example, the concentration of the metal salt solution may be 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L, 2 mol / L, etc. By making the concentration of the metal salt solution not less than 1 mol / L, it is possible to ensure that there are sufficient metal salt ions in the solution and reduce the drying and sintering time; by making the concentration of the metal salt solution not greater than 2 mol / L, it is possible to avoid the metal salt ion concentration being too high and the crystallization speed being too fast to be difficult to control.

[0068] According to some embodiments of the present invention, preparing the metal salt solution includes: dissolving a soluble metal salt in N,N-dimethylformamide at a fourth set temperature, and the fourth set temperature range is -20°C to 60°C. By dissolving the metal salt solution in N,N-dimethylformamide at the fourth set temperature, the metal salt solution can be maintained at the fourth set temperature before reacting with the organic ligand solution, ensuring that the metal salt solution is maintained at the fourth set temperature when subsequently mixed and reacted with the organic ligand solution.

[0069] The preparation of the organic ligand solution includes: dissolving the organic ligand raw material in N,N-dimethylformamide at a fourth set temperature. By dissolving the organic ligand raw material in N,N-dimethylformamide at the fourth set temperature, the organic ligand solution can be maintained at the fourth set temperature before reacting with the metal salt solution, ensuring that the organic ligand solution is maintained at the fourth set temperature when it is subsequently mixed with the metal salt solution and reacts.

[0070] According to some embodiments of the present invention, the fourth set temperature range is -5°C to 30°C. By setting the fourth set temperature range to -5°C to 30°C, the degree of lithium-nickel mixing in the positive electrode material can be reduced, resulting in better cycle performance of the battery.

[0071] According to some embodiments of the present invention, the metal salt solution and the organic ligand solution are mixed, including: pouring the metal salt solution into the organic ligand solution; stirring at a set speed for a fourth set time, the set speed range is 400rpm~600rpm, and the fourth set time range is 0.5h~1.5h. By controlling the fourth set temperature, the morphology of the material generated by the reaction of the organic ligand and the soluble metal salt can be controlled, thereby controlling the particle size of the precursor. By making the fourth set temperature not lower than -20°C, it can be avoided that the temperature is too low to cause the precursor particles to be too small, and the particles of the lithium salt are relatively too large to be fully and evenly mixed; by making the fourth set temperature not higher than 60°C, it can be avoided that the temperature is too high to cause the precursor particles to be too large, and the particles of the lithium salt are relatively too small to be fully and evenly mixed. Limiting the fourth set temperature to -20°C~60°C can make the particle size of the precursor moderate relative to the particle size of the lithium salt, and can be fully and evenly mixed with each other.

[0072] According to some embodiments of the present invention, the lithium salt includes at least one of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium acetate and lithium oxalate. For example, the lithium salt may be lithium hydroxide; for another example, the lithium salt may be a mixture of lithium hydroxide and lithium carbonate.

[0073] According to some embodiments of the present invention, the metal salts in the metal salt solution include soluble nickel salts, cobalt salts, and manganese salts; the organic ligand raw materials in the organic ligand solution include terephthalic acid. By making all three metal salts soluble salts, the three metals can be more easily dispersed and mixed with each other in water. By making the organic ligand raw materials in the organic ligand solution include terephthalic acid, the formed precursor can include metal-organic framework compounds.

[0074] According to some embodiments of the present invention, the nickel salt includes at least one of nickel sulfate, nickel acetate, nickel nitrate, nickel chloride, etc.; the cobalt salt includes at least one of cobalt sulfate, cobalt acetate, cobalt nitrate, cobalt chloride; the manganese salt includes at least one of manganese sulfate, manganese acetate, manganese nitrate, manganese chloride. For example, the nickel salt can be nickel sulfate, the cobalt salt can be cobalt sulfate, and the manganese salt can be manganese sulfate.

[0075] According to the positive electrode material of the second aspect embodiment of the present invention, the positive electrode material is prepared by the preparation method of the first aspect embodiment of the present invention, the positive electrode material has a single crystal structure, and the chemical formula of the positive electrode material is LiNi x Co y Mn z O2, where 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1. For example, the chemical formula of the positive electrode material can be LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0076] According to the positive electrode material of the embodiment of the present invention, it is prepared by using the preparation method of the first aspect embodiment of the present invention. After sintering, the precursor of the positive electrode material is not easily agglomerated, has good dispersibility, and has fewer intragranular microcracks in the positive electrode material, making the cycle performance of the battery better.

[0077] According to the battery of the third aspect embodiment of the present invention, it includes: a battery case and an electrode assembly. The electrode assembly is disposed in the battery case and includes stacked positive electrode sheets and negative electrode sheets. The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer coated on the positive electrode current collector. The positive electrode active material layer includes the positive electrode material of the second aspect embodiment of the present invention.

[0078] According to the battery of the embodiment of the present invention, by including the positive electrode material of the second aspect embodiment of the present invention, the precursor of the positive electrode material is not easily agglomerated after sintering, has good dispersibility, and has fewer intragranular microcracks in the positive electrode material, making the cycle performance of the battery better.

[0079] According to the electrical device of the fourth aspect embodiment of the present invention, it includes: the battery of the third aspect embodiment of the present invention.

[0080] The electric device according to the embodiment of the present invention comprises the battery according to the embodiment of the third aspect of the present invention, so the battery has better cycle performance and longer life.

[0081] The positive electrode materials of the embodiments of the present invention are further described below in combination with some embodiments and comparative examples.

[0082] 1. Preparation of materials.

[0083] (1) Preparation of positive electrode materials of various embodiments and comparative examples.

[0084] A nickel-cobalt-manganese positive electrode material is prepared. The nickel-cobalt-manganese positive electrode material of each of the following embodiments is prepared by the preparation method according to the embodiment of the first aspect of the present invention, and the nickel-cobalt-manganese positive electrode material of the comparative example is prepared by the preparation method in the related art.

[0085] Example 1: Weigh 0.954g Ni(CH3COO)2·4H2O, 0.1245g Co(CH3COO)2·4H2O and 0.1225g Mn(CH3COO)2·4H2O and dissolve them in 100mL DMF at 0°C. Weigh 0.8307g terephthalic acid and dissolve it in 50mL DMF at 0°C. At 0°C and 500rpm, the metal salt solution is quickly transferred to the DMF solution of terephthalic acid and aged for 1h. The solution is then washed several times with DMF and ethanol in a centrifuge and dried in a 60°C vacuum oven for 12h to obtain the precursor Ni 0.8 Co 0.1 Mn 0.1 -MOF. The precursor was first calcined at 500°C in oxygen for 3 hours, then ground and mixed with lithium salt, and sintered together at 780°C for 12 hours to obtain the nickel-cobalt-manganese ternary positive electrode material.

[0086] Example 2: Weigh 0.954g Ni(CH3COO)2·4H2O, 0.1245g Co(CH3COO)2·4H2O and 0.1225g Mn(CH3COO)2·4H2O and dissolve them in 100mL DMF at 25°C. Weigh 0.8307g terephthalic acid and dissolve it in 50mL DMF at 25°C. At 25°C and 500rpm, the metal salt solution is quickly transferred to the DMF solution of terephthalic acid and aged for 1h. The solution is then washed several times with DMF and ethanol in a centrifuge and dried in a 60°C vacuum oven for 12h to obtain the precursor Ni 0.8 Co 0.1 Mn 0.1 -MOF. The precursor was first calcined at 500°C in oxygen for 3 hours, then ground and mixed with lithium salt, and sintered together at 780°C for 12 hours to obtain the nickel-cobalt-manganese ternary positive electrode material.

[0087] Example 3: Weigh 0.954g Ni(CH3COO)2·4H2O, 0.1245g Co(CH3COO)2·4H2O and 0.1225g Mn(CH3COO)2·4H2O and dissolve them in 100mL DMF at 60°C. Weigh 0.8307g terephthalic acid and dissolve it in 50mL DMF at 60°C. At 60°C and 500rpm, the metal salt solution is quickly transferred to the DMF solution of terephthalic acid and aged for 1h. The solution is then washed several times with DMF and ethanol in a centrifuge and dried in a vacuum oven at 60°C for 12h to obtain the precursor Ni 0.8 Co 0.1 Mn 0.1 -MOF. The precursor was first calcined at 500°C in oxygen for 3 hours, then ground and mixed with lithium salt, and sintered together at 780°C for 12 hours to obtain the nickel-cobalt-manganese ternary positive electrode material.

[0088] Comparative Example 1: Polycrystalline precursor material Ni prepared by related technology 0.8 Mn 0.1 Co 0.1 (OH)2, according to TM:Li + 5 g of the polycrystalline precursor prepared by the related technology and 2.386 g of LiOH·H2O were weighed and ground in a ratio of =1:1.05, calcined at 500°C in oxygen for 3 h, then ground and mixed with lithium salt, and sintered together at 780°C for 12 h to obtain a nickel-cobalt-manganese ternary positive electrode material.

[0089] (2) Preparation of positive electrode sheets of various embodiments and comparative examples.

[0090] The nickel-cobalt-manganese ternary positive electrode material, conductive carbon black (Super-P) and a binder polyvinylidene fluoride (PVDF) containing N-methyl-2-pyrrolidone (NMP) prepared above were mixed in a mass ratio of 8:1:1, stirred for 0.5 h using a magnetic stirrer to obtain a positive electrode slurry, and the positive electrode slurry was evenly coated on one side of a clean aluminum foil surface, dried, and cut into pieces to obtain a positive electrode sheet for testing.

[0091] (3) Preparation of button-type half-cells of various embodiments and comparative examples.

[0092] In a glove box with a moisture and oxygen content of less than 10 ppm and filled with argon, the positive electrode sheet prepared as above was used, a lithium sheet was used as the negative electrode, an electrolyte of 1 mol / L LiPF6 (the solvent was EC:DMC:EMC=1:1:1) was added, and a polypropylene separator with a thickness of 20 μm was used to assemble a CR2032 button battery.

[0093] 2. Related tests

[0094] (1) XRD test was performed on the precursors before calcination of Example 1, Example 2, Example 3 and the precursor before calcination in Comparative Example 1.

[0095] Reference Figure 1 , Figure 1 XRD patterns obtained by XRD testing the precursors of Example 1, Example 2, Example 3 and the precursor of Comparative Example 1. As the preparation temperature increases, the peak of Ni / Co / Mn-MOF at 9.2° gradually weakens, the peak at 8.7° gradually strengthens, and the peak at 15.5° gradually strengthens. Figure 2 The precursor Ni of Example 1 is shown 0.8 Co 0.1 Mn 0.1 -The crystal structure of MOF before sintering is formed by nickel, cobalt and manganese metal atoms as nodes and terephthalic acid as organic ligands.

[0096] (2) The precursor Ni / Co / Mn-MOF of Example 1, Example 2 and Example 3 was subjected to electron microscope scanning to obtain SEM images of the precursors of Example 1, Example 2 and Example 3 before calcination.

[0097] Figure 3 This is the SEM image of the precursor Ni / Co / Mn-MOF, reference Figure 3 It can be seen that as the temperature of the mixed reaction of the metal salt solution and terephthalic acid increases, the morphology of Ni / Co / Mn-MOF changes from obvious lamellar materials stacked into spheres, and then changes to block or granular materials stacked into spheres, and the particle size of the spheres gradually increases.

[0098] (3) XRD test was performed on the positive electrode materials of Example 1, Example 2 and Example 3.

[0099] refer to Figure 4 , Figure 4 1 is the XRD diagram of ternary positive electrode material embodiment 1, embodiment 2 and embodiment 3. Figure 4 It can be seen from (a) that the characteristic peaks of the materials are all α-NaFeO2 structures of the R-3m space group, which can correspond to the characteristic peaks of the standard card PDF#74-0919. Figure 4In (b) and (c), it can be seen that the (006) / (102) and (018) / (110) splitting peaks of the three samples are obviously split, indicating that a good layered structure has been formed. The c / a ratios are all greater than 4.92, indicating that the three materials have formed an excellent hexagonal structure. The XRD of the three positive electrode materials was refined, and the unit cell parameters of the positive electrode materials were obtained as shown in Table 1. The I(003) / I(104) ratio of Example 3 is slightly less than 1.2, so its Li+ / Ni2+ mixing degree is relatively high, which is 10.40%. The I(003) / I(104) ratios of Examples 1 and 2 are both greater than 1.2, and their Li+ / Ni2+ mixing degrees are relatively low, only 2.60% and 4.20%. As the temperature of preparing Ni / Co / Mn-MOF increases, the degree of lithium-nickel mixing of the obtained ternary cathode material gradually increases. This may be because the spherical particles composed of the lamellar materials of Ni / Co / Mn-MOF prepared at low temperatures are smaller and more dispersed, and large-scale material agglomeration is avoided during the pre-sintering at 500°C to remove organic components. Less agglomeration can be more evenly mixed with lithium hydroxide during lithium mixing, and then the lithiation reaction can be better carried out during pulse high-temperature sintering, avoiding the lithium-nickel mixing promoted by high temperature during pulse high-temperature sintering.

[0100] Table 1

[0101]

[0102] (4) The positive electrode materials of Example 1, Example 2 and Example 3 were subjected to electron microscope scanning to obtain SEM images of Example 1, Example 2 and Example 3.

[0103] refer to Figure 5 , Figure 5 is the SEM image of the positive electrode materials of Example 1, Example 2 and Example 3, Figure 5 (a) is a SEM image of the positive electrode material of Example 1, Figure 5 (b) is a SEM image of the positive electrode material of Example 2, Figure 5 (c) is a SEM image of the positive electrode material of Example 3. It can be seen from the SEM image that the particle sizes of the three materials of Example 1, Example 2 and Example 3 are about 1 to 3 μm.

[0104] (5) The surface chemical environment of the elements in the positive electrode material of Example 1 was measured using X-ray photoelectron spectroscopy (XPS) to obtain an XPS spectrum.

[0105] refer to Figure 6 , Figure 6The XPS spectrum obtained by measuring the surface chemical environment of the elements in NCM-60 of Example 1 using X-ray photoelectron spectroscopy (XPS) shows that the binding energy peaks of Ni 2p3 / 2 and Ni 2p1 / 2 are 855.58eV and 873.08eV, respectively, and the two satellite peaks are 860.88eV and 879.38eV, respectively. The higher the binding energy of the Ni 2p3 / 2 peak, the higher the average valence state of the Ni ion. The binding energy peaks of Co 2p3 / 2 and Co 2p1 / 2 are 780.18eV and 795.08eV, respectively. The binding energy peaks of Mn2p3 / 2 and Mn 2p1 / 2 are 642.48eV and 653.88eV, respectively. The XPS data of the material using Avantage software were further peak separated and fitted. The main peak at 855.38eV belongs to Ni 2+ , the main peak at 856.38 eV belongs to Ni 3+ , where Ni 2+ The proportion of Ni is 50.18%, 3+ The peak at 780.18 eV belongs to Co 3+ , the peak at 781.78 eV belongs to Co 4+ , where Co 3+ The proportion of Co is 63.48%, 4+ The peak at 641.98 eV belongs to Mn 4+ . Due to the Co generated during sintering 4+ and Mn 4+ Less, so there is more Ni in the material 2+ Oxidized to Ni 3+ The possibility of lithium-nickel mixing is reduced.

[0106] (6) Example 1 was characterized by TEM, selected area electron diffraction (SEAD) and EDS Mapping to obtain a characterization graph of Example 1.

[0107] refer to Figure 7 , Figure 7 TEM, selected area electron diffraction (SEAD) and EDS Mapping are used to characterize the ternary cathode material of Example 1, wherein Figure 7 (a) is the TEM image of Example 1, Figure 7 (b) is an enlarged TEM image of Example 1, Figure 7 (c) and (d) are IFFT diagrams of Example 1. Figure 7 (e) is the HRTEM image of Example 1, Figure 7 (f) is the Mapping diagram of Example 1, Figure 7 (g) is the selected area electron diffraction pattern of Example 1. Figure 7 It can be seen from (a), (b), (c) and (d) that the lattice spacing of the sample is 0.2035nm, corresponding to the (104) crystal plane, and the other lattice spacing is 0.2465nm, corresponding to the (101) crystal plane. Figure 7 (e) and (f) show the EDS spectra of the material, and the Ni, Co, Mn and O elements are evenly distributed throughout the primary particles. Figure 7 The diffraction pattern in the SAED image of (g) is a hexagonal lattice, indicating that the material is a single crystal material. After calibration, the structure of the material is a hexagonal layered structure.

[0108] (7) The button cells in Example 1, Example 2, Example 3 and Comparative Example 1 were subjected to electrochemical performance tests. The electrochemical performance tests included:

[0109] The cycle performance test was carried out by charging to 4.5V at a constant current of 1.0C and then discharging to 2.5V at a constant current for 200 cycles at room temperature and 45°C. The cycle performance data at room temperature and 45°C were obtained, where the normal temperature was 25°C.

[0110] refer to Figure 8 and Fig. 9 , Figure 8 The cycle performance test results of the button-type batteries in Example 1, Example 2, Example 3 and Comparative Example 1 at 25° C. are shown. Fig. 9 The cycling performance of the four materials in a 45°C constant temperature box is demonstrated. It can be seen that the capacity of the four materials at a 1C rate is 221.51mAh / g, 215.62mAh / g, 184.16mAh / g and 186.01mAh / g. Before the 1C cycle, the four materials were subjected to three cycles of 0.1C formation. As the formation continued, the capacity of the materials gradually increased. After 100 cycles, the discharge specific capacities of the four materials were 135.07mAh / g, 127.53mAh / g, 107.43mAh / g and 73.93mAh / g, respectively, and the capacity retention rates were 60.98%, 59.15%, 58.34% and 39.75%, respectively.

[0111] (8) After 200 cycles, the button-type batteries in Example 1 and Comparative Example 1 were subjected to cross-sectional SEM to obtain cross-sectional SEM images of the positive electrode active material layer of the positive electrode.

[0112] refer to Fig.10 , Fig.10 (a) and (b) are cross-sectional SEM images of Example 1 after 200 cycles. Fig.10 (c) and (d) are cross-sectional SEM images of Comparative Example 1 after 200 cycles. Fig.10It can be seen that Example 1 can still maintain the initial structure after 200 cycles without obvious intracrystalline microcracks, while Comparative Example 1 has obvious microcracks along the grain boundaries in the center of the secondary particles.

[0113] In the description of the present invention, "first feature" or "second feature" may include one or more of the features.

[0114] In the description of the present invention, "plurality" means two or more.

[0115] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0116] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.

Claims

1. A method for preparing a positive electrode material, characterized in that: include: preparing a metal salt solution and an organic ligand solution; Mixing the metal salt solution and the organic ligand solution to form a suspension; Performing solid-liquid separation on the suspension to separate the precursor; Drying the precursor to obtain a precursor, wherein the precursor includes a metal organic framework compound; calcining the precursor; The calcined precursor and lithium salt are mixed and sintered to obtain the positive electrode material.

2. The method for preparing the positive electrode material according to claim 1, characterized in that: Before drying the precursor, the precursor is washed with an organic solvent.

3. The method for preparing the positive electrode material according to claim 2, characterized in that: The precursor is washed with an organic solvent, comprising: The precursor is washed with N,N-dimethylformamide and ethanol respectively.

4. The method for preparing the positive electrode material according to claim 1, characterized in that: The calcined precursor and lithium salt are mixed and sintered, comprising: In an oxygen atmosphere, heating to a first set temperature at a set heating rate, and sintering at the first set temperature for a first set time; The range of the set heating rate is 3°C / min to 8°C / min; the range of the first set temperature is 750°C to 900°C; and the range of the first set time is 6h to 10h.

5. The method for preparing the positive electrode material according to claim 1, characterized in that: calcining the precursor, including: calcining at a second set temperature for a second set time; The second set temperature ranges from 400° C. to 600° C., and the second set time ranges from 2 h to 4 h.

6. The method for preparing the positive electrode material according to claim 1, characterized in that: Mixing the precursor and the lithium salt includes grinding and mixing the lithium salt and the calcined precursor.

7. The method for preparing the positive electrode material according to claim 1, characterized in that: The drying process conditions for drying the precursor include: drying at a third set temperature for a third set time; The third set temperature ranges from 50°C to 70°C, and the third set time ranges from 10h to 14h.

8. The method for preparing the positive electrode material according to claim 1, characterized in that: The molar ratio of lithium ions in the lithium salt to metal ions in the metal salt solution is 1.02 to 1.08; and / or the concentration range of the metal salt solution is 1 mol / L to 2 mol / L.

9. The method for preparing the positive electrode material according to claim 1, characterized in that: The preparation of the metal salt solution comprises: dissolving a soluble metal salt in N,N-dimethylformamide at a fourth set temperature, wherein the fourth set temperature ranges from -20°C to 60°C; The method for preparing the organic ligand solution comprises: dissolving an organic ligand raw material in N,N-dimethylformamide at a fourth set temperature.

10. The method for preparing the positive electrode material according to claim 9, characterized in that: The fourth set temperature range is -5°C to 30°C.

11. The method for preparing the positive electrode material according to claim 1, characterized in that: The metal salt solution and the organic ligand solution are mixed, comprising: pouring the metal salt solution into the organic ligand solution; The mixture is stirred at a set speed for a fourth set time, wherein the set speed ranges from 400 rpm to 600 rpm, and the fourth set time ranges from 0.5 h to 1.5 h.

12. The method for preparing the positive electrode material according to claim 1, characterized in that: The lithium salt includes at least one of lithium hydroxide, lithium carbonate, lithium chloride, lithium nitrate, lithium acetate and lithium oxalate.

13. The method for preparing a positive electrode material according to any one of claims 1 to 12, characterized in that: The metal salt in the metal salt solution includes soluble nickel salt, cobalt salt and manganese salt; the organic ligand raw material in the organic ligand solution includes terephthalic acid.

14. The method for preparing the positive electrode material according to claim 13, characterized in that: The nickel salt includes at least one of nickel sulfate, nickel acetate, nickel nitrate and nickel chloride; the cobalt salt includes at least one of cobalt sulfate, cobalt acetate, cobalt nitrate and cobalt chloride; the manganese salt includes at least one of manganese sulfate, manganese acetate, manganese nitrate and manganese chloride.

15. A positive electrode material, characterized in that: The positive electrode material is prepared by the preparation method according to any one of claims 1 to 14, the positive electrode material is a single crystal structure and the chemical formula of the positive electrode material is LiNi x Co y Mn z O2, where 0 <x<1,0<y<1,0<z<1,x+y+z=1。 16. A battery, characterized in that: include: Battery housing; An electrode group is arranged in the battery casing and includes a stacked positive electrode sheet and a negative electrode sheet, the positive electrode sheet includes a positive electrode collector and a positive electrode active material layer coated on the positive electrode collector, and the positive electrode active material layer includes the positive electrode material according to claim 15.

17. An electrical device, characterized in that: include: A battery according to claim 16.

Citation Information

Cited By

  • Layered oxide positive electrode material, preparation method and sodium ion battery

    CN120398138A